Novel modified phase-shift modulation strategy for isolated AC-DC power converters - Llomplat, Marcelo (2020)
Different power converter topologies are used to perform the energy exchange between an AC grid and a DC source belonging to a hybrid electric micro-grid. A single-phase single-stage isolated AC-DC power converter is one of them. Moreover, this power converter can operate under different modulation strategies. The phase-shift modulation (PSM) strategy is capable of varying the phase between the voltages applied to the high-frequency transformer terminals of the power converter in order to control the energy flow in both directions. Based on the PSM strategy, this study presents a novel modified PSM strategy capable of controlling the power flow in both directions and obtaining a current with low total harmonic distortion and a power factor close to 1 for the entire operating range on the AC side. Considering the novel modulation strategy to be proposed, a comparison of three PSM-based modulation strategies was carried out taking into account the total harmonic distortion of current injected into the AC grid, the power factor and the average power transferred. A theoretical analysis was carried out and the results obtained were validated by means of experimental results.